2015
DOI: 10.4103/1817-1745.165709
|View full text |Cite
|
Sign up to set email alerts
|

Childhood-onset (Juvenile) Huntington′s disease: A rare case report

Abstract: Huntington's disease (HD) is a rare dominantly inherited neurodegenerative disorder characterized clinically by a combination of abnormal involuntary (choreic) movements, neuropsychiatric manifestations, and dementia. It is caused by an unstable CAG repeat expansion in the gene IT15 which encodes a Huntingtin protein. We present a case of a 9 year old boy who had developmental regression starting from the age of 8 years of age along with resistant seizures and signs of cerebellar involvement with absence of ch… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(12 citation statements)
references
References 17 publications
0
10
0
2
Order By: Relevance
“…His brain MR Spectroscopy demonstrated normal metabolite patterns. Some reports described brain MRIs that showed hyper intensity involving the caudate nucleus and putamen on both sides 19 Other studies reported subcortical nonspecific tbl2 hyper intense lesions, particularly in patients with the rigid, more than the classical hyperkinetic form. 20 Cerebral volumetric loss has also been described in the basal ganglia, thalami, hippocampi, substantia nigra, and cerebellum with varying degrees of atrophy correlating with the disease stage.…”
Section: Discussionmentioning
confidence: 99%
“…His brain MR Spectroscopy demonstrated normal metabolite patterns. Some reports described brain MRIs that showed hyper intensity involving the caudate nucleus and putamen on both sides 19 Other studies reported subcortical nonspecific tbl2 hyper intense lesions, particularly in patients with the rigid, more than the classical hyperkinetic form. 20 Cerebral volumetric loss has also been described in the basal ganglia, thalami, hippocampi, substantia nigra, and cerebellum with varying degrees of atrophy correlating with the disease stage.…”
Section: Discussionmentioning
confidence: 99%
“…In contrast to our findings, several smaller case studies of patients with JOHD reported smaller cerebellar volumes. 2931 These studies are limited by their smaller sample size and confounded by the presence of epilepsy in the majority of their patients. Only 20% of patients in our JHD cohort had a history of seizures.…”
Section: Discussionmentioning
confidence: 99%
“…Um estudo com 29 pacientes possuindo herança paterna mostrou que estes tendem a ter antecipação da doença e um maior número de repetições, consequentemente distúrbios mais graves 13 , o que é reforçado por um outro estudo que comparou adultos com DH e jovens com DHJ, chegando à conclusão que os mais novos possuem maior instabilidade da expansão CAG e progressão mais rápida da doença¹. Os autores também reforçam que o início dos sintomas pode cursar com alterações na função executiva e desempenho escolar, depressão, ansiedade e distúrbios de movimento 2,4,5,7,8,15,16 , bem como que as convulsões apresentadas pelos pacientes podem ser mistas de diferentes tipos 17 . Outro sintoma, que se assemelha à DH adulta, consiste nos movimentos oculares sacádicos alterados, que podem estar relacionados diretamente com a gravidade da DHJ 14 .…”
Section: Dicussãounclassified
“…Dentre as alterações de imagem, foram constatadas evidentes atrofias cerebelar 2,5,7,9,13 , de núcleos caudado e putâmen (corpo estriado) 1,5,7,10,16 na grande maioria dos pacientes, com significativo alargamento ventricular 5,10 em alguns, que se evidenciam com a evolução do quadro, não sendo encontrados em diagnósticos precoces. Quanto aos achados de RM, as medidas de volume intracraniano se apresentaram reduzidas 19 .…”
Section: Dicussãounclassified